Prevalence of aphasia and dysarthria among inpatient stroke survivors: describing the population, therapy provision and outcomes on discharge. Issue 7 (3rd July 2021) - Mitchell, Claire; Gittins, Matthew; Tyson, Sarah; Vail, Andy; Conroy, Paul; Paley, Lizz; Bowen, Audrey
ABSTRACT: Background : Stroke causes communication impairments but we lack the real-world population-level data needed to inform inpatient and community services. Aims: To establish prevalence of aphasia and dysarthria within inpatient stroke survivors, describe those affected, the amount of therapy they receive and their outcomes. Methods & Procedures : Secondary analysis of data from the Sentinel Stroke National Audit Programme, England, Wales and Norther Ireland, including inpatient stroke survivors after 72 hours, with completed National Institute of Health Stroke Scale data (communication items), excluding those already discharged, not conscious or with incomplete data. Outcomes & Results : 64% of the 88, 974 stroke survivors meeting our criteria were communication impaired: 28% had both aphasia and dysarthria, 24% had dysarthria only and 12% had aphasia only. Those in the older age range and with more severe stroke were more likely to have a communication impairment and had a worse outcome than those without communication impairment. On average, those with both communication impairments had a 21 day length of stay and 10 minutes of speech and language therapy for communication and/or dysphagia per day of stay. Conclusions : Communication impairment is common during the inpatient phase of stroke care yet average therapy provision is below the recommended levels and is likely to include dysphagia assessment and intervention. Dysarthria is reported as more prevalent than aphasia at this early stage, although this is not necessarily diagnosed by a speech and language therapist. The most common presentation is to have a combination of aphasia and dysarthria for which there is limited clinical guidance.